Factor VII Deficiency in Systemic Mastocytosis with an Associated Myeloid Neoplasm - Giorgio Rosati; Sofia Camerlo; Alessandro Fornari; Valerio Marci; Barbara Montaruli; Alessandro Morotti (Hematology Reports, 2024)
Factor VII (FVII) deficiency is a rare bleeding disorder that can be classified as congenital or acquired, and the majority of acquired cases are due to vitamin K deficiency or liver disease. Isolated acquired FVII deficiency is a rare occurrence and has been associated with inhibitors or auto-antibodies. Here, we describe a patient with polycythemia vera who developed systemic mastocytosis and FVII deficiency simultaneously. FVII deficiency was not caused by inhibitors and improved with antineoplastic treatment. Acquired FVII deficiency has been reported in cases of sepsis, possibly due to proteolytic degradation induced by the activation of monocytes or endothelial cells. Malignancies have been shown to cause a depletion in circulating FVII through the direct binding of cancer cells. This case report suggests a potential association between SM associated with a hematological neoplasm (SM-AHN) and acquired FVII deficiency. Further evaluations are recommended in patients with systemic mastocytosis to gain a better understanding of the relationship between pathological mast cells and clotting factor concentrations.